Biological activities of selected Malaysian seaweeds / Shuba a/p Salvam - Salvam, Shuba (2009)
Antioxidant activity of nine seaweeds, two microalgae, two teas, two dried fruit skins and one dried flower were determined. Among the seaweeds extracts, Sargassum binderi showed the highest AOx (antioxidant activity) for its boiled water extract in both AEAC (ascorbic acid equivalence antioxidant capacity) and DPPH (Diphenyl-1-picrylhydrate) assays. Methanolic extracts of Sargassum binderi and Padina tetrastromatica showed the highest AOx in DPPH and AEAC assays respectively. Gracilaria changii showed the highest AOx for its methanolic extract in Galvinoxyl assay. Boiled water extract of Padina tetrastromatica showed the highest total phenolic content in Total Phenolic assay. The two microalgae tested were Spirulina platensis and Chlorella vulgaris where the former showed highest AOx for its boiled water extract in AEAC and Total phenolic assays while the latter showed higher AOx in AEAC, Galvinoxyl and Total Phenolic assays for its methanol extract. The other samples studied also showed AOx in all the assays tested for their boiled water and methanolic extracts. It was determined in this study that storage, drying and grinding method, as well as the solvent used on samples influenced AOx. Ethyl acetate (PT Ea) and ethanol (PT Et) extracts of Padina tetrastromatica and Kappaphycus alvarezii ethanol (KA Et) extracts chosen for animal studies showed that they significantly reduced inflammation, pain and ulcer lesions (except for PT Ea that was not used in the ulcer study) but were concentration dependent. PT Ea showed the highest LD50 (1845 mg/kg) followed by PT Et (1596 mg/kg) and KA Et (1799 mg/kg). The seaweeds studied showed antioxidant, anti-inflammatory, antinociceptive and anti-ulcerogenic activities. These seaweeds could be useful for their biological activities.